Infectiousness of Leishmania major to Phlebotomus papatasi: differences between natural reservoir host Meriones shawi and laboratory model BALB/c mice. - Barbora Vojtková; Tomáš Bečvář; Lenka Pacáková; Daniel Frynta; Nalia Mekarnia; Kamal Eddine Benallal; Petr Volf; Jovana Sádlová (PLoS Neglected Tropical Diseases)
Host infectiousness to insect vectors is a crucial parameter for understanding the transmission dynamics of insect-borne infectious diseases such as leishmaniases. Despite their importance, critical factors influencing the outwards transmission of Leishmania major, including parasite distribution within the host body and the minimum number of skin amastigotes required for vector infection, remain poorly characterized. To address these gaps, we studied these parameters in the natural North African reservoir host Meriones shawi and in BALB/c mice infected with a low parasite dose. Using qPCR, we quantified Leishmania loads in different zones (regions) of infected ear pinnae, whereas microscale infectiousness was evaluated via microbiopsies and fluorescence microscopy. The amastigote distribution within infected ears was heterogeneous, with pronounced differences between the lesion center, lesion margin, and visually unaffected surrounding skin. Phlebotomus papatasi females that fed in areas where no amastigotes were detected via microscopy did not become infected. In M. shawi, lesion margins have emerged as the most effective source of infection. The number of amastigotes at bite sites where sand fly females became infected ranged from 4--500, with as few as 2--10 amastigotes sufficient to initiate vector infection. This low infection threshold was confirmed by experiments in which P. papatasi was fed through a chick-skin membrane. In contrast, the BALB/c mouse model showed only minor differences in infectiousness between lesion centers and margins. The minimum infectious dose in BALB/c mice was approximately 100 times greater than that in M. shawi, with successful infections occurring at sites containing 1,500-10,000 amastigotes. These findings advance our understanding of Leishmania transmission by addressing critical knowledge gaps and enabling more accurate modelling of cutaneous leishmaniasis epidemiology. Moreover, this study highlights the importance of incorporating natural host models in research, as the dynamics of disease progression and transmission parameters can differ significantly between natural hosts and standard laboratory models.